The impact of alternative grade configurations on student outcomes through middle and high school - Guido Schwerdt; Martin R. West (Center for Economic Studies and ifo Institute (CESifo), 2011)
We use statewide administrative data from Florida to estimate the impact of attending public schools with different grade configurations on student achievement through grade 10. To identify the causal effect of structural school transitions, we use student fixed effects and instrument for middle and high school attendance based on the terminal grade of the school attended in grades 3 and 6, respectively. Consistent with recent evidence from other settings, we find that students moving from elementary to middle school in grade 6 or 7 suffer a sharp drop in student achievement in the transition year. We confirm that these achievement drops occur in nonurban areas and persist through grade 10, by which time most students have transitioned into high school. We also find that middle school entry increases student absences and is associated with higher grade 10 dropout rates. Transitions to high school in grade nine cause a smaller one-time drop in achievement but do not alter students' performance trajectories.
Keywords: H52; I21; I28; 330; educational production; public schools; grade configuration; middle schools; high schools; Bildungsniveau; Weiterführende Schule; Bildungsökonomik; Florida